A poetics of postmodernism : history, theory, fiction - Hutcheon, Linda, 1947- (Routledge, 1988)
Neither a defense nor a denunciation of the postmodern, it continues Hutcheon's previous projects in studying formal self-consciousness in art, but adds to this both a historical and ideological dimension.